Molecular and Functional Covariance Statistics demonstrate Network Reorganization in Parkison's Disease: a multimodal PET-fMRI study - Santos, Diliana Maria Barradas Rebelo dos (2020)
Trabalho Final do Mestrado Integrado em Medicina apresentado à Faculdade de Medicina